THE DEVELOPMENT OF THE CHARITY RETAIL SECTOR IN THE UK - Nguyen, Thanh Ha (2011)
The charity shop model has become a retail phenomenon in the UK. The first shop opened in 1945 and there are 9,000 shops open in 2011 that seek to generate unallocated income for charitable purposes. Despite the success of the charity retail sector little research has been carried out to identify the key factors in its development.